The Financial and Operating Performance of Newly Privatized Firms: An International Empirical Analysis - Megginson, William L.; Nash, Robert C.; Randenborgh, Matthias van (Journal of Finance, 1994)
This study compares the pre and postprivatization financial and operating performance of 61 companies from 18 countries and 32 industries that experience full or partial privatization through public share offerings during the period 1961 to 1990. Our results document strong performance improvements, achieved surprisingly without sacrificing employment security. Specifically, after being privatized, firms increase real sales, become more profitable, increase their capital investment spending, improve their operating efficiency, and increase their work forces. Furthermore, these companies significantly lower their debt levels and increase dividend payout. Finally, we document significant changes in the size and composition of corporate boards of directors after privatization.